2015
DOI: 10.15537/smj.2015.9.12369
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of quantity and quality of biomedical publications in Gulf Cooperation Council countries from 2011-2013

Abstract: Objectives:To compare the research productivity of different Gulf Cooperation Council (GCC) countries in the field of biomedical sciences from 2011-2013.Methods:This is a retrospective study conducted in the College of Medicine, Alfaisal University, Riyadh, Saudi Arabia. Data on the biomedical publications originating from GCC countries published between January 2011 to December 2013 was searched via MEDLINE using PubMed. The total number of publications emanating from each country was normalized with the coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…As reported previously, the average impact factor of journals that publish the articles of medical students in our institute was 2.4 [10]. We also recently reported a large analysis based on PubMed, indexed research articles by GCC country, and the average impact factor for all the GCC countries (which is 1.6) [18]. The current figure in this study is higher, demonstrating that medical students' research articles do not differ in quality from those reported by faculty members in the GCC countries.…”
Section: Discussionsupporting
confidence: 73%
“…As reported previously, the average impact factor of journals that publish the articles of medical students in our institute was 2.4 [10]. We also recently reported a large analysis based on PubMed, indexed research articles by GCC country, and the average impact factor for all the GCC countries (which is 1.6) [18]. The current figure in this study is higher, demonstrating that medical students' research articles do not differ in quality from those reported by faculty members in the GCC countries.…”
Section: Discussionsupporting
confidence: 73%
“…Bibliometric analysis of the publications and journals is being increasingly used to measure the quality and quantity of publications in a specific area, country, or region including the Arab world. 11 - 17 Before the introduction of the JIF, the quality of the journal was gauged arbitrarily, based on the parameters like how long it was established, reputation of that journal, the strictness of the peer review, and the acceptance rate. With the assignment of a numerical value to represent the quality of a journal, fierce competition among the journals has been witnessed.…”
Section: Discussionmentioning
confidence: 99%
“… 10 This encouragement has led to significant academic and research activities, launching of various scientific journals, and growth of publications. 10 In our previous study, 11 we measured the research output in terms of quantity and quality in KSA over the last 5 years. However, it would be equally interesting to measure the performance of the Saudi biomedical journals.…”
mentioning
confidence: 99%
“…Nearly 7,000 MEDLINE ® -listed research papers have been published from these countries over the past ten years. 3 Kuwait and Saudi Arabia also featured among the top ten countries, with regard to biomedical research productivity in Asia. 4 In spite of the active research profile of the GCC countries, to the best of our knowledge there is no formal training course that prepares the biomedical scientists in these countries to undertake animal research in line with the international standards on animal ethics, Good Laboratory Practice (GLP) or FELASA guidelines.…”
Section: Biomedical Research In Gulf Co-operation Council Countriesmentioning
confidence: 99%